Transformasi Pembelajaran Dasar Melalui Media Interaktif: Sebuah Telaah Literatur Terhadap Dampaknya pada Hasil Belajar - Raudatul Saumi; Ari Suriani (Jurnal Yudistira : Publikasi Riset Ilmu Pendidikan dan Bahasa, 2025)
This study aims to explore the impact of interactive learning media on elementary school students' learning outcomes in the context of the Merdeka Curriculum. Interactive learning media includes educational videos, game-based applications, and digital platforms that encourage active participation and more meaningful learning. This study uses a literature review method involving 11 studies from 2016 to 2024. The results show that interactive media positively influence students' cognitive, affective, and psychomotor achievements. It is also proven effective in supporting differentiated learning and increasing learning motivation. These findings provide important implications for the development of more relevant, adaptive, and responsive learning strategies to students' needs in the digital era.